Indonesian Workers Require “Diuwongke” to be engaged - Rahmadani, Vivi Gusrini; Machfiroh, Nurul; Maahiroh, Mega; Fauzia, Rahma; Meilona, Ridhoi (PROCEEDING SERIES OF PSYCHOLOGY, 2024)
This research determines the impact of “diuwongke” on work engagement among plantation workers at an agriculture company in Indonesia. This is a quantitative correlational survey method with a cross-sectional design. 368 plantation workers voluntarily participated in this study who worked on several areasin North Sumatra, Indonesia. The instruments used to collect the data consist of Utrecht Work Engagement Scale (UWES) and “Diuwongke” Scale. While work engagement describes as employees’ positive psychological state toward their job, diuwongke is a local indigenous concept of Indonesia, developed by Rahmadani & Schaufeli (2022). A simple regression method with IBM SPSS Statistic Ver.25 was performed to analyze the data. The findings indicate that there is a positive and significant relationship between “diuwongke” and work engagement (r= 0.449, p < 0.05), moreover, “diuwongke” contributed to explaining 20.1% of the variance in work engagement. To summarize, the higher the level of “diuwongke” perceived by the plantation workers, the stronger their work engagement. This study emphasizes the importance of good relationships between leaders and followers in a country with a high power distance national culture. Leaders, who have power and authority, play a key role in creating leaders-followers positive work relationships through how they treat their followers.